2015
DOI: 10.1007/s10384-015-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

Macular ischemia and outcome of vitrectomy for diabetic macular edema

Abstract: Vitrectomy is an effective treatment modality for DME refractory to nonsurgical therapies, especially in cases without enlarged FAZ. Preoperative evaluation of the perfusion status of the macula seems helpful to selecting candidates for vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…PPV itself has been widely used to treat tractional or refractory DME (40)(41)(42)(43), which relieves DME through multiple mechanisms, including the elimination of traction factors (44), improving intravitreal oxygenation, removing pathological cytokines (such as VEGF) in the vitreous cavity, and accelerating the half-life of intravitreal cytokines (45). Whereas the low incidence of postoperative DME after PPV, there are few studies on the risk factors for postoperative DME in patients with PDR.…”
Section: Discussionmentioning
confidence: 99%
“…PPV itself has been widely used to treat tractional or refractory DME (40)(41)(42)(43), which relieves DME through multiple mechanisms, including the elimination of traction factors (44), improving intravitreal oxygenation, removing pathological cytokines (such as VEGF) in the vitreous cavity, and accelerating the half-life of intravitreal cytokines (45). Whereas the low incidence of postoperative DME after PPV, there are few studies on the risk factors for postoperative DME in patients with PDR.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, vitrectomy can be an alternative treatment. Several previous studies have reported the efficacy of vitrectomy for treatment-refractory DME [10][11][12][28][29][30] . The studies agree that vitrectomy helps reduce macular thickness in refractory DME, but improvement of visual acuity after vitrectomy has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Four (9%) subjects did not achieve resolution of macular edema and underwent additional treatment after 3 months postoperatively. www.nature.com/scientificreports/ vitrectomy for refractory DME is beneficial in both reducing CMT and improving visual acuity [10][11][12][29][30][31] . In contrast, in a large prospective study from the Diabetic Retinopathy Clinical Research Network (DRCR.net), vitrectomy was beneficial for reducing CMT; however, its efficacy for improving visual acuity was limited 28 .…”
Section: Figurementioning
confidence: 99%
“…Pars plana vitrectomy (PPV) remains a viable option in the treatment regimen for DMO and plays a role, especially in the context of managing concomitant DMO and vitreomacular interface disturbance [198]. Even in the absence of the most serious complications of proliferative diabetic retinopathy (vitreous haemorrhage and retinal detachment), there is considerable evidence that vitrectomy reduces macular oedema in patients with DMO, especially in those with clinically evident signs of a taut, thickened posterior hyaloid [199][200][201][202][203][204][205][206][207]. Furthermore, vitrectomy has an acceptable risk profile compared with anti-VEGF therapy considering rates of major complications for each procedure [208].…”
Section: Surgerymentioning
confidence: 99%